(untitled) (New York, 1994)
Providing authoritative texts, introductions and informative notes for students, the 4th edition of this anthology includes many more complete works such as "Billy Budd", "Ethan Frome" and "Daisy Miller", as well as a varied selection of drama
Keywords: American literature